Preparation and application of a coated‐fiber needle extraction device. Issue 19 (14th September 2016) - Lou, Dawei; Chen, Huijun; Wang, Xiyue; Lian, Lili; Zhu, Bo; Yang, Qiaoling; Guo, Tingxiu; Li, Qiuying; Wang, Runnan; Guo, Xiaoyang
Abstract : In this study, a needle‐trap device with fibers coated with a molecularly imprinted polymer was developed for separation. A number of heat‐resistant Zylon filaments were longitudinally packed into a glass capillary, followed by coating with a molecularly imprinted polymer. Then, the molecularly imprinted polymer coating was copolymerized and anchored onto the surface of the fibers. The bundle of synthetic fibers coated with the molecularly imprinted polymer was packed into a 21G stainless‐steel needle and served as an extraction medium. The coated‐fiber needle extraction device was used to extract volatile organic compounds from paints and gasoline effectively. Subsequently, the extracted volatile organic compounds were analyzed by gas chromatography. Calibration curves of gaseous benzene, toluene, ethylbenzene, and o ‐xylene in the concentration range of 1–250 μg/L were obtained to evaluate the method, acceptable linearity was attended with correlation coefficients above 0.998. The limit of detection of benzene, toluene, ethylbenzene, and o ‐xylene was 11–20 ng/L using the coated‐fiber needle‐trap device. The relative standard deviation of needle‐to‐needle repeatability was less than 8% with an extraction time of 20 min. The loss rates after storage for 3 and 7 days at room temperature were less than 30%.